Avaliação de pastagens de capim elefante consorciadas com diferentes leguminosas - Seibt, Daiane Cristine (2015)
The milk production systems, mostly, use the pastures as the main source of forage for cattle, usually, consisting only of grasses. This strategy simplifies the management of pastures, however, implies high production costs, notably the high use of nitrogen fertilizers. An alternative to become the pasture systems more sustainable is the introduction of forage legumes, allowing a better distribution forage mass over time and reduce fertilizer costs. Thus, the objective of this research was to evaluate of three grazing systems (GS) with elephant grass (EG), Italian ryegrass (IR) and spontaneous growing species (SGS), as GS1 (control); EG + IR + SGS + arrowleaf clover, as GS2; and EG + IR + SGS + forage peanut, as GS3; during a crop year. The elephant grass was established in rows with a distance of 4m between rows. In winter period, Ryegrass was sowed between rows of EG; and considering respective treatments the arrowleaf clover was sowed and the forage peanut was preserved. Lactating Holstein cows were used in the evaluation. Experimental design was completely randomized with three treatments (grazing systems), three replicates (paddocks) with repeated measures (grazing cycles/seasons). Eight grazing cycles were performed during the experimental period (365 days), two in each season. The forage mass, botanical composition; daily accumulation dry matter rate, production and forage intake; grazing efficiency, stocking rate and nutritive value were evaluated. Samples from hand-plucking method were collected to analyze neutral detergent fiber (NDF), crude protein (CP), in situ dry matter digestibility (ISDMD) and total digestible nutrients (TDN). The values of forage mass and stocking rate were 3.46, 3.80 and 3.91 t ha-1 and 2.89, 3.39 and 3.20 animal unit ha-1, respectively for GS. Better results were found on grazing systems mixed with forage legumes. The average of NDF, CP, ISDMD and TDN of EG were 62.4, 61.5 and 60.2 %; 16.7, 16.7 and 18.1 %; 79.6, 79.8 and 79.1 %; 71.4, 71.2 and 69.9 %; and of the forage between rows of EG were 60.3, 60.3 and 52.4 %; 13.7, 15.7 and 19.5 %; 75.0, 72.8 and 81.1 %; 67.9, 65.3 and 72.9 %, respectively for treatments. Higher value of CP, ISDMD and TDN and lower of NDF were observed for the grazing systems mixed with forage peanut, especially on winter. Better results to nutritive value of elephant grass were found on spring.